Pelestarian Lokal Melalui Penyusunan Teks Negosiasi dalam Pembelajaran Bahasa Indonesia (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines efforts to preserve local wisdom, which aims to describe students' and teachers' perceptions, identify challenges, and analyze the process of compiling negotiation texts. Implemented at SMA Karya Ibu Palembang in April-May 2025 with a qualitative approach, data were obtained through surveys and interviews. The results showed that students and teachers had positive perceptions of this activity, although some students experienced vocabulary and topic determination problems. The majority of students succeeded in compiling texts with good structures, but aspects of creativity and language accuracy still need development. This initiative contributed significantly to the preservation of Palembang Malay and improving students' language skills.